Take logarithm on both sides and use the exponent rule of logarithms:
log(ab) = b*log(a)
So applying the rule to the given equation:
log(3^(x+4)) = log(2^(1-3x))
(x+4)log(3) = (1-3x)log(2)
Solve the resulting linear equation after substituting numerical values of log(3) and log(2). You can use either natural log (to the base e) or common log (to the base 10).
I get x=-1.2 approximately.
i'm sorry i don't understand the last part :(
Evaluate log(3) and log(2) using logarithm to the base 10.
log103 = 0.4771
log102 = 0.3010